Calcium ion-induced in-situ construction of Janus structure broadband wave-absorbing material and preparation and application thereof
Patent Information
- Application Number
- CN202610927171.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-25
- Publication Date
- 2026-10-16
AI Technical Summary
所制备的Janus磁碳材料无需依赖高导电填料即可实现优异的阻抗匹配并显著拓宽有效吸收带宽,同时借助Ca2+调控优化磁损耗、介电损耗与界面极化损耗,显著拓宽有效吸收带宽并提升结构稳定性,进而解决了现有技术在双金属MOF体系中构筑Janus结构形貌调控与宽频吸收难以协调、制备工艺复杂等难题
(1)本发明先采用溶剂热法合成前驱体,再通过一步热解工艺处理,最终获得四种不同Ni/Ca比例的Ni基双金属MOF衍生Janus磁碳复合材料;该制备过程操作简便、成本可控,能一步实现钙离子诱导原位构筑Janus结构;
Smart Images

Figure CN122934759A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of broadband absorbing materials technology, and relates to a broadband absorbing material with a calcium ion-induced in-situ Janus structure, its preparation and application. Background Technology
[0002] With the rapid development of 5G communication, flexible electronics, and intelligent equipment technologies, electromagnetic interference is becoming increasingly severe, creating an urgent need for lightweight, wide-bandwidth, high-efficiency, low-reflection, and high-stability absorbing materials. While traditional magnetic / dielectric composite materials can achieve synergistic magnetic-dielectric loss, they generally suffer from bottlenecks such as poor impedance matching, strong high-frequency reflection, weak low-frequency absorption, and insufficient structural stability. Therefore, developing a novel Janus magnetic carbon material that requires no high-reflection filler, can spontaneously form an asymmetric structure in situ, and possesses strong magnetic coupling, low reflection, and wide-bandwidth high-efficiency absorption has significant scientific and practical value.
[0003] Asymmetric Janus structures, with their unique morphological anisotropy, abundant heterojunctions, and multiple polarization sites, can significantly enhance interfacial polarization, dipole polarization, and multiple reflection and scattering of electromagnetic waves, making them ideal structures for overcoming broadband absorption bottlenecks. However, current methods for constructing Janus structures still lack simple, continuous, and quantifiable morphological control, especially in bimetallic MOF systems. It is difficult to achieve controllable evolution from symmetric ellipsoids to asymmetric Janus structures through differences in metal ion coordination behavior, thus limiting the structural design and performance improvement of high-frequency broadband absorbing materials. To address these challenges, this study proposes a method based on Ca... 2+ A novel strategy for ion-controlled geometry and in-situ construction of Janus magnetic carbon systems. (Using Ca...) 2+ Ion-induced asymmetric structural evolution in the magnetic carbon precursor achieves a synergistic unity of morphological asymmetry, enhanced magnetic domain coupling, and strengthened interfacial polarization. The prepared Janus magnetic carbon material achieves excellent impedance matching and significantly broadens the effective absorption bandwidth without relying on highly conductive fillers, while also leveraging Ca... 2+ By regulating and optimizing magnetic loss, dielectric loss, and interface polarization loss, the effective absorption bandwidth is significantly broadened and the structural stability is improved.
[0004] For example, Chinese patent CN122002777A provides a method for preparing a functionalized graphene-based composite absorbing material with wideband and high efficiency electromagnetic wave absorption. This absorbing material uses graphene (Gr) prepared by electrochemical exfoliation as a conductive matrix, followed by functionalization. A Gr / FeOOH intermediate is prepared by loading needle-like ferrite FeOOH onto its surface using a solution method, and then a layer of flower-shaped molybdenum disulfide (MoS2) is coated onto the surface of the intermediate using a one-step hydrothermal method. However, the electromagnetic wave absorption performance of this Gr / FeOOH@MoS2 composite material still has significant shortcomings. Its effective absorption bandwidth cannot fully cover the ultra-wideband 2–18 GHz, achieving high efficiency absorption only within a limited frequency range. This fails to meet the practical requirements of modern electronic equipment and complex electromagnetic environments for full-band, strong attenuation, and high-stability electromagnetic protection.
[0005] For example, the cobalt-manganese-iron alloy-carbon composite microwave absorbing material provided in Chinese patent application CN116583097A uses a cobalt-manganese-iron alloy-carbon composite microwave absorbing material. It prepares a metal-organic framework material CoMnFe-MOF-74 through a solvothermal reaction, and then calcines it in a protective atmosphere. By adjusting the ratio of cobalt, manganese, and iron and the reaction conditions, multiple loss mechanisms and excellent microwave absorption performance are achieved. This patent changes the microstructure of the material by adjusting the metal ratio and reaction conditions. Its precursor is a single-morphology MOF-74, lacking precise control over the final morphology of the product, and thus failing to solve the problem of coordinating broadband absorption and structural control in existing technologies. Summary of the Invention
[0006] The purpose of this invention is to provide a broadband microwave absorbing material with a calcium ion-induced in-situ Janus structure, its preparation and application, through Ca... 2+ Ion-induced asymmetric structural evolution in the magnetic carbon precursor achieves a synergistic unity of morphological asymmetry, enhanced magnetic domain coupling, and strengthened interfacial polarization. The prepared Janus magnetic carbon material achieves excellent impedance matching and significantly broadens the effective absorption bandwidth without relying on highly conductive fillers, while also leveraging Ca... 2+ By regulating and optimizing magnetic loss, dielectric loss, and interfacial polarization loss, the effective absorption bandwidth is significantly broadened and the structural stability is improved. This solves the problems of existing technologies in constructing Janus structures in bimetallic MOF systems, such as the difficulty in coordinating morphological control and broadband absorption, and the complexity of fabrication processes.
[0007] This invention synthesizes a precursor via a solvothermal method, followed by a one-step pyrolysis treatment. By systematically adjusting the Ni / Ca molar ratio (e.g., 5:1, 4:2, 3:3, and 2:4), a clear and continuous evolution of the bimetallic MOF morphology can be achieved, successively evolving from an ellipsoid to a Janus lotus-shaped structure, then to a Janus spiky lotus-shaped structure, and finally forming a symmetrically separated Janus configuration. This intuitively reveals the core role of the metal ion ratio in regulating crystal nucleation, growth, and morphology. The process produces an NCC-x composite material characterized by a Janus hierarchical structure that constructs abundant heterogeneous interfaces and defect sites, significantly enhancing dielectric losses such as interfacial polarization and dipole polarization, while retaining the magnetic losses of the Ni-based component, achieving a synergistic improvement in electromagnetic loss performance; the spiky structure further increases the multiple reflection and scattering paths of electromagnetic waves, optimizing impedance matching characteristics.
[0008] The objective of this invention can be achieved through the following technical solutions: In a first aspect, the present invention provides a method for preparing a broadband absorbing material with a calcium ion-induced in-situ Janus structure, comprising the following steps: S1. Dissolve 2,5-dihydroxyterephthalic acid and polyvinylpyrrolidone in a solution containing N,N-dimethylformamide, ethanol and deionized water to obtain a mixed solution. Add metal salts (i.e., soluble Ni salt and soluble Ca salt) to the above mixed solution, stir, transfer to a polytetrafluoroethylene-lined counter-pressure reactor for reaction, centrifuge after reaction, wash, and dry to obtain Ni-Ca-MOF precursor; S2. The Ni-Ca-MOF precursor prepared in S1 is calcined in a reducing atmosphere to obtain the NCC-x composite material (x=1,2,3,4, where x=1 when Ni:Ca=5:1; x=2 when Ni:Ca=4:2; x=3 when Ni:Ca=3:3; and x=4 when Ni:Ca=2:4), which is the target product, the broadband absorbing material.
[0009] Furthermore, in S1, the mass ratio of 2,5-dihydroxyterephthalic acid to polyvinylpyrrolidone is (1~2):(2.6~4.2). The mass-to-volume ratio of N,N-dimethylformamide, ethanol, and deionized water is 1:1:1.
[0010] Furthermore, in S1, the soluble Ni salt is nickel nitrate or its hydrate, and the soluble Ca salt is calcium nitrate or its hydrate nickel nitrate. The amounts of the two metal salts added satisfy the Ni... 2+ Ca 2+ The molar ratio is 5:1 to 2:4, and can be selected as 5:1, 4:2, 1:1, etc. At the same time, the molar ratio of 2,5-dihydroxyterephthalic acid to metal salt is 1:1.
[0011] Furthermore, in S1, the temperature of the solvothermal reaction is 120~150℃, and the time is 7~10h.
[0012] Furthermore, in S1, the centrifugation speed is 8000~9000 r / min, and the centrifugation time is 1~5 min.
[0013] Furthermore, in S1, the washing process involves sequentially washing with deionized water and ethanol solution, and the washing is repeated 3 to 5 times.
[0014] Furthermore, in S1, the drying is vacuum drying, and the drying temperature is 60~80℃.
[0015] Furthermore, in S2, the reducing atmosphere is provided by an H2 / Ar mixture, specifically a mixture of 5% hydrogen and 95% argon by volume.
[0016] Furthermore, in S2, the calcination temperature is 600~700℃ and the time is 2~5h.
[0017] In a second aspect, the present invention provides a broadband absorbing material with a calcium ion-induced in-situ Janus structure, which is prepared by the preparation method described in the first aspect above.
[0018] Furthermore, the broadband microwave absorbing material with calcium ion-induced in-situ Janus structure can achieve a clear and continuous evolution of the bimetallic MOF morphology by adjusting the molar ratio of lithium ions to calcium ions, successively evolving from an ellipsoid to a Janus lotus-shaped structure, then to a Janus thorn-like lotus-shaped structure, and finally forming a symmetrically separated Janus configuration.
[0019] In a third aspect, the present invention provides an application of a broadband absorbing material with a calcium ion-induced in-situ Janus structure in the field of broadband microwave absorption.
[0020] This invention, through systematic control of the Ni / Ca molar ratio, achieved a continuous evolution of the morphology of the bimetallic MOF from an ellipsoidal shape to a Janus structure, revealing the core regulatory role of the metal ion ratio in crystal nucleation, anisotropic growth, and desymmetry processes. The results show that the prepared NCC-x samples exhibit excellent electromagnetic wave absorption performance, with the Ni / Ca=3:3 spiky lotus-shaped structure achieving an ultra-wide effective absorption bandwidth of 11.68–18.00 GHz (covering approximately 63% of this frequency band). This superior performance is attributed to the abundant heterogeneous interfaces and defect sites provided by the Janus hierarchical structure, significantly enhancing interface polarization and dipole polarization effects while retaining the magnetic loss of the Ni-based component, achieving a synergistic improvement in electromagnetic loss performance. Furthermore, the spiky morphology further extends the multiple reflection and scattering paths of electromagnetic waves, ultimately achieving a synergistic enhancement between structural design, impedance matching, and absorption performance. In addition, this material also demonstrates outstanding stealth, tensile strength, and thermal conductivity, and is expected to provide a reference for future research and design of designable, high-performance electromagnetic pollution control and electromagnetic protection materials.
[0021] Compared with the prior art, the present invention has the following advantages: (1) The present invention first uses a solvothermal method to synthesize the precursor, and then processes it through a one-step pyrolysis process to finally obtain four Ni-based bimetallic MOF-derived Janus magnetic carbon composite materials with different Ni / Ca ratios; the preparation process is simple to operate and cost-controllable, and can realize calcium ion-induced in-situ construction of Janus structure in one step. (2) In this invention, by systematically controlling the Ni / Ca molar ratio, the morphology of the bimetallic MOF has achieved a continuous evolution from ellipsoidal to Janus structure, revealing the core regulatory role of the metal ion ratio in crystal nucleation, anisotropic growth and desymmetry process.
[0022] (3) In this invention, small-sized Ni nanoparticles and carbon nanotubes form a higher density interface contact, thereby constructing a rich Ni / C heterostructure interface, which greatly enhances the interface polarization. At the same time, the small size effect of Ni particles can enhance surface anisotropy, break the traditional Snoek limit, maintain high permeability at high frequencies, and improve the absorption of high-frequency electromagnetic waves. (4) The Janus multilevel structure in this invention provides abundant heterogeneous interfaces and defect sites, which significantly enhances the interface polarization and dipole polarization effects, while retaining the magnetic loss of the Ni-based component, thus achieving a synergistic improvement in electromagnetic loss performance. In addition, the spiked morphology further extends the multiple reflection and scattering paths of electromagnetic waves, ultimately achieving a synergistic enhancement between structural design, impedance matching and absorption performance. Among them, the spiked lotus-shaped structure with Ni / Ca=3:3 achieves an ultrawide effective absorption bandwidth of 11.68~18.00GHz (covering about 63% of this frequency band). Attached Figure Description
[0023] Figure 1 A schematic diagram showing the morphology and application of broadband absorbing materials based on calcium ion-induced in-situ construction of Janus structures; Figure 2 The images show the XRD patterns of samples from Examples 1, 2, 3, and 4. Figure 3 SEM images of samples from Examples 1, 2, 3, and 4; Figure 4 The diagram shows the reflection loss of samples in Examples 1, 2, 3, and 4. Figure 5 These are simulated radar cross sections of samples from Examples 1, 2, 3, and 4. Figure 6 SEM images of the samples prepared for Comparative Example 1 and Comparative Example 2; Figure 7 The image shows the microwave absorption performance of the samples prepared for Comparative Example 1 and Comparative Example 2. Detailed Implementation
[0024] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. These embodiments are based on the technical solution of the present invention and provide detailed implementation methods and specific operating procedures. However, the scope of protection of the present invention is not limited to the following embodiments.
[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application.
[0026] As used herein, the terms "and / or," "or / and," and "and / or" encompass any one of two or more of the related listed items, as well as any and all combinations of the related listed items. These arbitrary and all combinations include any two related listed items, any more related listed items, or a combination of all related listed items. It should be noted that when at least three items are connected using at least two conjunctions selected from "and / or," "or / and," and "and / or," it should be understood that, in this application, the technical solution undoubtedly includes solutions connected by "logical AND," and also undoubtedly includes solutions connected by "logical OR."
[0027] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.
[0028] In this application, numerical ranges are referred to as continuous unless otherwise specified, and include the minimum and maximum values of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.
[0029] This document only specifically discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, just as any upper limit can be combined with any other upper limit to form an unspecified range. Furthermore, each individually disclosed point or single value can itself serve as a lower or upper limit and be combined with any other point or single value or with other lower or upper limits to form an unspecified range.
[0030] Unless otherwise specified, the temperature parameters in this application may be either constant temperature processing or processing within a certain temperature range. The constant temperature processing allows temperature fluctuations within the precision range controlled by the instrument, such as ±5℃, ±4℃, ±3℃, ±2℃, or ±1℃.
[0031] In this document, the term "suitable" as used in phrases such as "suitable combination," "suitable method," and "any suitable method" refers to the ability to implement the technical solution of this application, solve the technical problem of this application, and achieve the expected technical effect of this application.
[0032] In this application, terms such as "further," "even further," and "particularly" are used to describe purposes and indicate differences in content, but should not be construed as limiting the scope of protection of this application.
[0033] In this application, "optionally," "optionally," and "optional" mean that something is optional, that is, it means that it is selected from either "with" or "without." If there are multiple "optional" entries in a technical solution, unless otherwise specified, and there are no contradictions or mutual constraints, each "optional" entry shall be independent.
[0034] In the description of the application, "multiple" means at least two, such as two, three, etc., unless otherwise explicitly specified.
[0035] Unless otherwise specified, all preparations and tests described herein took place at 25°C.
[0036] The terms “comprising,” “including,” “containing,” “having,” “comprising,” or other variations thereof are intended to cover non-closed inclusion, and no distinction is made between these terms. The term “comprising” means that other steps and ingredients may be added without affecting the final result. The compositions and methods / processes of the present invention comprise, consist of, and substantially consist of the essential elements and limitations described herein, as well as any additional or optional ingredients, components, steps, or limitations described herein. No distinction is made between the terms “efficacy,” “performance,” “effect,” and “potency” herein.
[0037] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions. Unless otherwise specified, all technical features and optional technical features of this application can be combined to form new technical solutions.
[0038] Unless otherwise specified, all steps of this application may be performed sequentially or randomly, but sequentially is preferred.
[0039] In the following embodiments, unless otherwise specified, the raw materials or processing techniques are conventional commercially available raw materials or conventional processing techniques in the art.
[0040] Example 1: The preparation steps of NCC-1, a broadband microwave absorbing material with a Janus structure induced by calcium ions in situ, are as follows: (1) Dissolve 2,5-dihydroxyterephthalic acid (0.4g) and polyvinylpyrrolidone PVP-K30 (1.05g) in 30mL of equal volumes of N,N-dimethylformamide, ethanol and deionized water, and stir magnetically to obtain a homogeneous mixed solution. Weigh nickel nitrate hexahydrate (0.4856g) and calcium nitrate tetrahydrate (0.0779g), stir magnetically for 30min, and then transfer the solution to a 50mL polytetrafluoroethylene-lined counter-pressure reactor. React at 100℃ for 10 hours. After centrifugation, washing and vacuum drying, Ni-Ca-MOF is obtained.
[0041] (2) The Ni-Ca-MOF prepared in step (1) was calcined at 700℃ for 2 hours in a reducing atmosphere with a heating rate of 5℃ / min to obtain the NCC-1 composite material, which is denoted as NCC-1.
[0042] Example 2: Compared with Example 1, most of the results were the same, except that the amount of nickel nitrate hexahydrate added was changed to 0.3897g and the amount of calcium nitrate tetrahydrate added was changed to 0.1559g. The resulting product was designated as NCC-2.
[0043] Example 3: Compared with Example 1, most of the results were the same, except that the amount of nickel nitrate hexahydrate added was changed to 0.2908 g and the amount of calcium nitrate tetrahydrate added was changed to 0.2362 g. The resulting product was designated as NCC-3.
[0044] Example 4: Compared with Example 1, most of the results were the same, except that the amount of nickel nitrate hexahydrate added was changed to 0.1919 g and the amount of calcium nitrate tetrahydrate added was changed to 0.3164 g. The resulting product was designated as NCC-4.
[0045] like Figure 2 The figure shows the XRD characterization of the NCC-x absorbing material prepared according to the embodiments of the present invention. The sample numbers NCC-1 / NCC-2 / NCC-3 / NCC-4 in the figure correspond to Examples 1, 2, 3, and 4, respectively. After pyrolysis, all samples retain the characteristic peak of Ni, and a broad characteristic peak appears near 25°, corresponding to the formation of amorphous carbon.
[0046] like Figure 3 As shown, the NCC-x microwave absorbing material prepared in the embodiments of the present invention was characterized by SEM. By adjusting the Ni / Ca molar ratio (from 5:1 to 2:4, corresponding to a to d respectively), the morphology of the bimetallic MOF achieved a continuous evolution from a uniform ellipsoid → Janus lotus shape → Janus spiky lotus shape → symmetrical separated Janus structure.
[0047] like Figure 4 As shown, a) is the absorption performance diagram of NCC-1 obtained in Example 1, with an effective absorption bandwidth of 2.8 GHz within a thickness of 1-5 mm (2-8 GHz); b) is the absorption performance diagram of NCC-2 obtained in Example 2, with an effective absorption bandwidth of 4.0 GHz within a thickness of 1-5 mm (2-8 GHz); c) is the absorption performance diagram of NCC-3 obtained in Example 3, with an effective absorption bandwidth of 6.3 GHz within a thickness of 1-5 mm (2-8 GHz); d) is the absorption performance diagram of NCC-4 obtained in Example 4. Figure 4 Within a thickness of 1–5 mm, the effective absorption bandwidth of 2–8 GHz is 5.7 GHz.
[0048] like Figure 5 As shown, the simulated radar cross section of the NCC-x absorbing material prepared in this embodiment of the invention is illustrated, wherein the maximum RCS value of NCC-3 is 37.4 dB·m. 2 This indicates that NCC-x has excellent radar stealth performance.
[0049] Comparative Example 1: Compared with Example 3, most of the contents are the same, except that Ca(NO3)2 is replaced with an equimolar amount of Ni(NO3)2 to synthesize Ni / C microwave absorbing material.
[0050] Comparative Example 2: Compared with Example 3, most of the results are the same, except that Ca(NO3)2 is replaced with an equimolar amount of cobalt nitrate to synthesize NiCo / C microwave absorbing material.
[0051] The morphologies and microwave absorption properties of Ni / C and NiCo / C prepared in Comparative Examples 1 and 2 are as follows: Figure 6 and Figure 7 .
[0052] The morphologies of Ni / C and NiCo / C obtained in Comparative Example 1 and Comparative Example 2 are shown in the figures respectively. Figure 6 As shown in a and b, both have a spindle-shaped morphology, proving that only Ca(NO3)2 can regulate the morphology and structure of Ni-MOF to form a special Janus structure.
[0053] The microwave absorption properties of Ni / C prepared in Comparative Example 1 are as follows: Figure 7 As shown in Figure a, within a thickness of 1–5 mm, the effective absorption bandwidth in the range of 2–18 GHz is 4.86 GHz.
[0054] The microwave absorption properties of NiCo / C prepared in Comparative Example 2 are as follows: Figure 7 As shown in Figure b, within a thickness of 1–5 mm, the effective absorption bandwidth in the range of 2–18 GHz is 5.36 GHz.
[0055] Combination Figure 7 By comparing Example 3 with Example 4, it can be concluded that calcium ion-induced in-situ construction of Janus structure is beneficial to broaden the effective absorption band and improve the absorption performance, while traditional Ni / C and NiCo / C cannot obtain a wide absorption band.
[0056] The above description of the embodiments is provided to enable those skilled in the art to understand and use the invention. It will be apparent to those skilled in the art that various modifications can be made to these embodiments, and the general principles described herein can be applied to other embodiments without inventive effort. Therefore, the present invention is not limited to the above embodiments, and any improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the invention should be within the protection scope of the present invention.
Claims
1. A method for preparing a broadband microwave absorbing material with a calcium ion-induced in-situ Janus structure, characterized in that, Includes the following steps: S1. Dissolve 2,5-dihydroxyterephthalic acid and polyvinylpyrrolidone in a mixed solvent containing N,N-dimethylformamide, ethanol and deionized water to obtain a mixed solution. Then add soluble Ni salt and soluble Ca salt, stir, transfer to a counter-pressure reactor for reaction, centrifuge after reaction, wash and dry to obtain Ni-Ca-MOF precursor. S2. The Ni-Ca-MOF precursor prepared in S1 is calcined in a reducing atmosphere to obtain a broadband absorbing material.
2. The method for preparing a broadband absorbing material with a calcium ion-induced in-situ Janus structure according to claim 1, characterized in that, In S1, the mass ratio of 2,5-dihydroxyterephthalic acid to polyvinylpyrrolidone is (1~2):(2.6~4.2).
3. The method for preparing a broadband absorbing material with a calcium ion-induced in-situ Janus structure according to claim 1, characterized in that, In S1, the soluble Ni salt is nickel nitrate or its hydrate, and the soluble Ca salt is calcium nitrate or its hydrate. The addition amounts of the soluble Ni salt and the soluble Ca salt satisfy the following: the molar ratio of Ni2+ to Ca2+ is (5~2):(1~4); and the molar ratio of 2,5-dihydroxyterephthalic acid to the total amount of soluble Ni salt and soluble Ca salt is 1:
1.
4. The method for preparing a broadband absorbing material with a calcium ion-induced in-situ Janus structure according to claim 1, characterized in that, In S1, the reaction temperature is 120~150℃ and the time is 7~10h.
5. The method for preparing a broadband absorbing material with a calcium ion-induced in-situ Janus structure according to claim 1, characterized in that, In S1, the centrifugation speed is 8000~9000 r / min, and the centrifugation time is 1~5 min.
6. The method for preparing a broadband absorbing material with a calcium ion-induced in-situ Janus structure according to claim 1, characterized in that, In S1, the drying is performed under vacuum at a temperature of 60-80℃.
7. The method for preparing a broadband absorbing material with a calcium ion-induced in-situ Janus structure according to claim 1, characterized in that, In S2, the reducing atmosphere is provided by a mixture of hydrogen (5% by volume) and argon (95% by volume).
8. The method for preparing a broadband absorbing material with a calcium ion-induced in-situ Janus structure according to claim 1, characterized in that, In S2, the calcination temperature is 600~700℃ and the time is 2~5h.
9. A broadband microwave absorbing material with a calcium ion-induced in-situ Janus structure, characterized in that, It is prepared by the preparation method described in any one of claims 1-8.
10. The application of the broadband microwave absorbing material with a calcium ion-induced in-situ Janus structure as described in claim 9 in the broadband microwave absorption field of 11.68~18.00 GHz.
Citation Information
Patent Citations
Cobalt-manganese-iron alloy-carbon composite wave-absorbing material as well as preparation method and application thereof
CN116583097A
Preparation method of functionalized graphene-based composite wave-absorbing material capable of broadband and efficiently absorbing electromagnetic waves
CN122002777A